AB0556 Reumasex – sexual satisfaction and factors limiting sexual activity in patients with spondyloarthritis. (23rd January 2014) - Aguiar, R.; Ambrósio, C.; Cunha, I.; Barcelos, A.
Abstract : Background: The impact of rheumatic diseases on patients' sexual life has been gathering the attention of the scientific community over the last decade 1 . However, specific assessemnt tools are scarce and there are few existing studies, specially those related to spondyloarthritis 2 and particularly to psoriatic arthritis. In fact, several factors may condition sexual function in these patients: pain, stiffness, decreased range of motion, joint swelling and extraarticular features such as fatigue, enthesopathy and, in the case of psoriatic arthritis, cutaneous lesions. Objectives: To assess sexual satisfaction in a cohort of patients with spondyloarthritis; to identify the limitation imposed by different factors related to the disease in sexual activity; to search for relations between those limitation and quality of life and disease activity and function indexes. Methods: An anonymous questionnaire was performed, consisting in two parts. One part consisted in a questionnaire filled by the physician with data on the disease – affected joints, extraarticular features, comorbidities, current treatment, metrology in patients with axial involvement, disease activity (BASDAI and/or DAS28) and function (BASFI and HAQ) indexes and quality of life index (ASQoL). The other part consisted in a questionnaire filled by the patient, with demographic data (sex, age, disease duration, civil status, professional status and educational level), multiple choice questions and questions to be answered through a visual analogical scale, including items approached in some validated indexes of sexual function and satisfaction assessment. Statistical treatment was performed using SPPS system, version 17.0. Results: 95 patients with the diagnosis of spondyloarthritis were enrolled and 76 answered the questionnaire; 31 had psoriatic arthritis, 30 had ankylosing spondylitis, 9 had undifferentiated spondyloarthritis and 6 had inflammatory bowel disease spondyloarthritis; 40 were male, 35 were female and 1 unknown. Mean age was 46.08±12.08 and mean disease duration was 12.17±10.32 years. In a visual analogical scale, the mean sexual satisfaction level was 52.28±30.99; the perception of conditioning in the conjugal relationship was 33.68±31.56; limitation on sexual activity was 32.72±31.06; limitation by pain, joint swelling, fatigue, stiffness, decreased range of motion, decreased libido and psoriasis lesions varied from 29.17±28.51 (swelling) e 46.94±32.31 (fatigue), and there was no significant difference between sexes, diagnoses and type of involvement. A strong correlation was identified between most of these factors and ASQoL and HAQ values, but not between them and activity indexes. The presence of comorbidities did not influence the obtained values in a statistically significant way. Conclusions: This work highlights the impact of spondyloarthritis on patients' sexual function. Fatigue was mentioned as the most limiting factor in sexual activity, and the values obtained had a strong correlation with quality of life index in ankylosing spondylitis and with function index in psoriatic arthritis. The type of disease and joint involvement didn't imply statistically significant differences on the analyzed parameters in this cohort of patients. References: Tristano AG. The impact of rheumatic diseases on sexual function. Rheumatol Int 2009;29:853–60. Bal S et al. Sexual functions in ankylosing spondylitis. Rheumatol Int 2011;31(7):889-94. Disclosure of Interest: None Declared